Design for Change: Mindful Improvement Ideas - Fikri, Miftahul; Nurulhaq, Dadan (Atthulab: Islamic Religion Teaching and Learning Journal, 2023)
The purpose of writing this article is to find out the study of the Design for Change approach, to improve morals and care. The research method used is library research on a qualitative approach, data collection with documentation and analysis with content analysis. The results of this study are that Design for Change consists of four steps, namely Feel which feels the surrounding conditions, Image which imagines what will be done, Do which does what is planned, and Share which shares what has been done. Morals are formed by instinct, habituation and environment. Caring is influenced by culture, espoused values, price obtained, exclusivity and level of maturity. The conclusion from this research is that the Design for Change approach will form habits that improve awareness. Â Tujuan penulisan artikel ini adalah untuk mengetahui kajian pendekatan Design for Change, untuk memperbaiki akhlak dan kepedulian. Metode penelitian yang digunakan adalah library research pada pendekatan kualitatif, pengumpulan data dengan dokumentasi dan analisis dengan analisis konten. Hasil penelitian ini adalah Design for Change terdiri dari empat Langkah, yaitu Feel yang merasakan kondisi sekitar, Image yang membayangkan apa yang akan dilakukan, Do yang melakukan apa yang direncanakan, dan Share yang membagikan apa yang sudah dilakukan. Akhlak dibentuk oleh naluri, pembiasaan dan lingkungan. Kepedulian dipengaruhi oleh budaya, nilai yang dianut, harga yang didapat, keeksklusifan dan level kematangan. Simpulan dari penelitian ini adalah pendekatan Design for Change akan membentuk pembiasaan yang memperbaiki kepedulian.